Carrier-envelope phase stable few-cycle laser system delivering more than 100 W, 1 mJ, sub-2-cycle pulses - Haedrich Steffen (OPTICS LETTERS, 2022)
Two-stage multipass-cell compression of a fiber-chirpedpulse amplifier system to the few-cycle regime is presented. The output delivers a sub-2-cycle (5.8 fs), 107W average power, 1.07 mJ pulses at 100kHz centered at 1030nm with excellent spatial beam quality (M-2 =1.1, Strehl ratio S = 0.98), pointing stability (2.3 mu rad), and superior long-term average power stability of 0.1% STD over more than 8 hours. This is combined with a carrier-envelope phase stability of 360mrad in the frequency range from 10Hz to 50kHz, i.e., measured on a single-shot basis. This unique system will serve as an HR1 laser for the Extreme Light Infrastructure Attosecond Light Pulse Source research facility to enable high repetition rate isolated attosecond pulse generation. (C) 2022 Optica Publishing Group